Exploring HR Collaborative Initiatives in Opening Global Market Access for MSMEs - Budi Wahono; Budi Eko Soetjipto (International Forum of Researchers and Lecturers, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, but only 15.7% have successfully penetrated the global market due to limited human resources (HR) and cross-sector collaboration (BPS, 2023). This study aims to analyse the role of collaborative HR initiatives in opening global market access for MSMEs in East Java, using a quantitative approach with AMOS-based Structural Equation Modeling (SEM) on a sample of 150 MSMEs. The results of the analysis show that HR collaboration across sectors (government, private sector, academia) has a significant effect on improving global market access , while self-training is not significant. The findings strengthen the Resource-Based View theory by emphasising collaborative HR as a strategic asset of MSMEs. Practical implications include integrated policy recommendations and partnerships with global platforms (e.g., Amazon, Alibaba), as well as ethical considerations related to programme inclusivity and MSME data protection. This research makes a theoretical contribution to the development of an adaptive HR collaboration model for MSMEs in developing countries.